2012
DOI: 10.1039/c2cc33218c
|View full text |Cite
|
Sign up to set email alerts
|

Utilising tetraphenylethene as a dual activator for intramolecular charge transfer and aggregation induced emission

Abstract: We report a simple design and synthesis of a donor-acceptor tetraphenylethene-naphthalimide (TPE-NI) dyad, in which TPE acts both as an electron-donor for intramolecular charge transfer (ICT) and activator for aggregation induced emission (AIE). Strong solvent-dependent photoluminescence covering almost the whole visible spectrum and AIE in its nanoparticle state compared to its solution state are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(70 citation statements)
references
References 30 publications
1
67
0
Order By: Relevance
“…[16,[25][26][27] Quite a few molecules based on naphthalimide have been designed and used in optical sen-sors and OLEDs in recent years. [16,[25][26][27] Quite a few molecules based on naphthalimide have been designed and used in optical sen-sors and OLEDs in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…[16,[25][26][27] Quite a few molecules based on naphthalimide have been designed and used in optical sen-sors and OLEDs in recent years. [16,[25][26][27] Quite a few molecules based on naphthalimide have been designed and used in optical sen-sors and OLEDs in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The red shift and decrease in emission with the increase of solvent polarity (SI Appendix, Figs. S1 and S2) is indicative of a twisted intramolecular charge-transfer process upon photoexcitation from the donor (piperazinyl ring) to the acceptor (fluoroquinolone ring) (34,35), a process that is stabilized and promoted by polar solvents, however, susceptible to nonradiative quenching (36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] Despite the fact that π-π stacking between π-conjugated molecules generally leads to photoluminescence (PL) quenching, several specific π-conjugated organic molecules such as tetraphenylethylene (TPE) and cyanostilbene have demonstrated anomalous properties in which emission is enhanced in concentrated solution or solid-state but is quenched in solution. [1][2][3][4] It has been reported that these AIE features originated from the restricted intramolecular rotation in aggregation state of π-conjugated molecules. Over the past few years, many attempts have been made to develop efficient AIE-active materials having extraordinary properties for various applications geared towards organic semiconducting lasers, photochromic optical memory, fluorescence chemo/biosensors, organic light-emitting diodes, and organic transistors.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules exhibit twisted structures due to internal steric repulsion between larger aryl groups in dilute solution, while present planar structures due to tight π-π intermolecular packing in concentrated solution or in the solid state. [1][2][3][4] Among the various diarylalkene motifs, our interest lies in AIE-active molecules having unsymmetrically aryl-substituted alkene units, such as cyanostilbene. [9] These molecules may undergo typical E/Z isomerization under ultraviolet (UV) or visible irradiation.…”
Section: Introductionmentioning
confidence: 99%